Աշուղական համքարությունը որպես ավանդական պրոֆեսիոնալ երաժշտության զարգացման կենտրոն - Հարությունյան, Հասմիկ
Համքարությունը` որպես աշուղների գործունեության և կենսապահովման համակարգ սահմանող կառույց, մի կողմից՝ շարունակել է հայ միջնադարյան գուսանական արվեստի, մյուս կողմից՝ յուրացրել մերձավոր արևելյան բանավոր ավանդույթի դասական երաժշտության ավանդույթները: Այսպես. աշուղի ստեղծագործության մեջ առաջնային համարվող բանաստեղծական տեքստն ու տաղաչափությունը հնարավորություն են տվել դրանք եղանակավորելու ըստ նախընտրության, քանի որ վարպետ աշուղը ազատ է եղել երաժշտական բաղադրիչի ընտրության մեջ և ստեղծագործության կամ ելույթի համապատասխան պահի ընտրել է իր ուզած եղանակը: Цех, как структура, определяющая систему деятельности и жизнеобеспечения ашугов с одной стороны продолжил традиции искусства армянских средневековых гусанов, а с другой - ассимилировала классические музыкальные традиции ближневосточной устной традиции. Таким образом поэтический текст и метрика, считающиеся первичными в творчестве ашуга, позволяли корректировать их по предпочтениям, ведь мастер ашуг был свободен в выборе музыкальной составляющей и выбирал нужный ему лад в нужный момент произведения или речи. Методы и материалы: Историко-сравнительными и историкомузыковедческоими методоми были рассмотрены важные факты, связанные с жизнью и деятельностью ашугов. Анализ: Как показали архивные материалы, профессиональные знания ашугов согласовывались в цехе, не ограничивая их свободных и творческих преобразований и проявлений модернизации. Это относилось как к жанрам песен, так и метрике поэтических текстов. Результаты: В цехе ашугов все согласовывался в коллективном сотрудничестве, не ограничивая их свободных и творческих преобразований и проявлений реализации. Это относилось как к песенным жанрам, так и поэтическим текстам․ Тrade union as a structure defining the system of activity and livelihood of the ashughs, on the one hand continued the Armenian medieval Gusan art, and on the other hand, assimilated the classical music traditions of the Middle Eastern oral tradition. Thus. the poetic text and the metric, which are considered primary in the work of ashugh, made it possible to adjust them according to preference, because the master ashugh was free in the choice of the musical component and chose the mode he wanted at the appropriate moment of the work or performance. Methods and materials: With the help of historical-comparative and historical-musicological methods, important facts related to the life of the troupes were observed. Analysis: With the help of historical-comparative and musicological methods, the canonical thematic material preserved as much as possible in the interpretations of musical instruments, mainly mughams, was observed, revealing the versatile technical performance possibilities of the instrument. Results: As the archival materials have shown, the specialized knowledge of the troupes was coordinated in the troop coordination, without restricting their free and creative transformations and realizations. It applied both to the genres of songs and to the arrangement of poetic texts.
Keywords: Աշուղական արվեստ